If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + 5b + -7b = 0 Combine like terms: 5b + -7b = -2b 3a + -2b = 0 Solving 3a + -2b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2b' to each side of the equation. 3a + -2b + 2b = 0 + 2b Combine like terms: -2b + 2b = 0 3a + 0 = 0 + 2b 3a = 0 + 2b Remove the zero: 3a = 2b Divide each side by '3'. a = 0.6666666667b Simplifying a = 0.6666666667b
| n+n+1+n+2=27 | | 2(w-4)=8w+10 | | 6/7=x/10.5 | | 27x-3=51 | | 2a+8=3a-1 | | 51x-3=27 | | 5(x-2)=5x-11 | | 2(x+10)+3x=85 | | 51x-27=3 | | 32-5x=50-3x | | 5x+2(17-4x)=4 | | 3.2-0.5x=5-0.3x | | 4b+25+3b=-50 | | -11p+20p-6p-8p-p=16 | | -6(2x-1)=25 | | 3/4n-8=-17 | | 11/20-5/20= | | (4b+6)(6-4)= | | -15t+14t=7 | | x+x+1+x+2+x+3=-22 | | 3(2-2x)=2(4+5x) | | 0.8(x-4)=2(0.4x+1.6) | | 59=8y-9 | | 9x-2(4x+10)+2=21 | | 14g-10g-g=9 | | -13=5x+12 | | 80+x+(3x-22)=180 | | 0.5x+3x+0.6=180 | | 6r+7-9r-19= | | 3/4g=−12 | | -9-4=5x+12 | | 13+4-6n-2n=5-n+5n |